Now Peru Is Mine : The Life and Times of a Campesino Activist - Llamojha Mitma, Manuel, 1921-; Heilman, Jaymie Patricia (Book collections on Project MUSE., 2016)
Now Peru is Mine is the account of the life of Manuel Llamojha Mitma, one of Peru's most creative and inspiring indigenous political activists. His compelling life story covers nearly eight decades, providing a window into many key developments in Peru's tumultuous twentieth-century history and political mobilization in Cold War Latin America.